Miracles and Material Life : Rice, Ore, Traps and Guns in Islamic Malaya - Sevea, Teren, 1979- (Asian connections, 2020)
"In this ground-breaking new study, Teren Sevea reveals the economic, environmental and religious significance of Islamic miracle workers (pawangs ) in the nineteenth- and twentieth-century Malay world. Through close textual analysis of hitherto overlooked manuscripts and personal interaction with modern pawangs readers are introduced to a universe of miracle workers that existed both in the past and in the present, uncovering connections between miracles and material life. Sevea demonstrates how societies in which the production and extraction of natural resources, as well as the uses of technology, were intertwined with the knowledge of charismatic religious figures, and locates the role of the pawangs in the spiritual economy of the Indian Ocean world, across maritime connections and Sufi networks, and on the frontier of the British Empire"--